2017
DOI: 10.1182/blood-2017-05-782466
|View full text |Cite
|
Sign up to set email alerts
|

An aberrant NOTCH2-BCR signaling axis in B cells from patients with chronic GVHD

Abstract: B-cell receptor (BCR)-activated B cells contribute to pathogenesis in chronic graft-versus-host disease (cGVHD), a condition manifested by both B-cell autoreactivity and immune deficiency. We hypothesized that constitutive BCR activation precluded functional B-cell maturation in cGVHD. To address this, we examined BCR-NOTCH2 synergy because NOTCH has been shown to increase BCR responsiveness in normal mouse B cells. We conducted ex vivo activation and signaling assays of 30 primary samples from hematopoietic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 70 publications
16
67
0
Order By: Relevance
“…In that context it is important to understand which cell-intrinsic mechanisms enhance BCR responses. A novel observation here is that BCR responses to surrogate antigen were markedly increased when NOTCH2 was also activated 30 32 . Tregs are capable of selectively killing B-cells 33 and their deficiency would predispose to a failure to control pathogenic B-cells.…”
Section: The Role Of B-cells In Cgvhd -Evidence From Studies On Humanmentioning
confidence: 85%
“…In that context it is important to understand which cell-intrinsic mechanisms enhance BCR responses. A novel observation here is that BCR responses to surrogate antigen were markedly increased when NOTCH2 was also activated 30 32 . Tregs are capable of selectively killing B-cells 33 and their deficiency would predispose to a failure to control pathogenic B-cells.…”
Section: The Role Of B-cells In Cgvhd -Evidence From Studies On Humanmentioning
confidence: 85%
“…Furthermore, it is likely that these pathogenic immune cells emerge more rapidly in some HCT patients due to intrinsic signaling defects that are exacerbated due to continual exposure of developing cells to AlloAg and cytokines. Examples of this scenario in cGVHD include a paucity in Tregs and regulatory B cells (46, 60, 62, 67, 68), an increase in M2-like macrophages that express CSF-1R and invade the skin causing fibrosis (38), and B cells that have dysregulated expression of the key transcription factors IRF4 and IRF8, causing heightened signaling through NOTCH2, which synergizes with the BCR to induce abnormally high proliferative responses to limiting amounts of antigen (52). Emerging evidence suggests that some of these intrinsic defects that drive immune cell pathogenicity can be corrected pharmacologically, steering developing immune cells down either regulatory pathways or more mature functional pathways (3,9,45,47,52,69).…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH2 is a surface molecule and co‐stimulator of aberrant BCR responses in cGVHD. Poe et al () revealed increased NOTCH2‐BCR signalling and a decreased IRF4/IRF8 expression ratio in cGVHD. Increased NOTCH2 activation heightens BCR responsiveness and promotes the expression of the proximal BCR protein BLNK in cGVHD patients.…”
Section: Aberrant B Cell Pathwaysmentioning
confidence: 99%